2011
DOI: 10.1179/1362171810y.0000000013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of solidification mechanism on microstructure and mechanical properties of joint in TLP bonded Al2024‐T6 alloy

Abstract: Transient liquid phase (TLP) bonding of Al2024-T6 alloy, using gallium (Ga) interlayer, has been investigated. Bonding process was carried out at 470uC for 6 min, and homogenising temperature and time were 495uC and 2 h respectively. Conventional TLP bonding using Ga interlayer was not an appropriate method for joining of Al2024. In this method, the boundary between two Al2024 specimens was not fully eliminated during bonding because of solidification with planar front. In addition, bonding zone was depleted o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…where l max is the maximum thickness of the liquid interlayer region at the end of widening and homogenization, D is the diffusion coefficient of the liquid interlayer in solid substrate, K is the constant which can be derived from Lesoult's demonstration. 8 In this case of TLP diffusion bonding, it has been shown D (the diffusivity of Cu) was increased with increasing bonding temperature then resulted t IS for bonding was decreased. In this study, with using nanostructured structure that resulting short isothermal solidification time because diffusion time depends on the grain size.…”
Section: Microstructure Of Jointmentioning
confidence: 78%
See 2 more Smart Citations
“…where l max is the maximum thickness of the liquid interlayer region at the end of widening and homogenization, D is the diffusion coefficient of the liquid interlayer in solid substrate, K is the constant which can be derived from Lesoult's demonstration. 8 In this case of TLP diffusion bonding, it has been shown D (the diffusivity of Cu) was increased with increasing bonding temperature then resulted t IS for bonding was decreased. In this study, with using nanostructured structure that resulting short isothermal solidification time because diffusion time depends on the grain size.…”
Section: Microstructure Of Jointmentioning
confidence: 78%
“…As a result, these particles are accumulated in grain boundaries and in centreline of bonding zone in which the last stage of isothermal solidification specially occurs. 8 The results indicated that the width of the Al 2 O 3 particles concentration at the interface increased to approximately twice as the bonding temperature was increased from 550 to 610uC. This was attributed to an increase in the diffusivity of Cu from the interface into the base metal as the bonding temperature increased.…”
Section: Microstructure Of Jointmentioning
confidence: 91%
See 1 more Smart Citation
“…As is known that the micromechanical properties are related to the solidification process. [40,41] Therefore, we detected the micromechanical properties of solid gallium at different conditions.…”
Section: Micromechanical Propertiesmentioning
confidence: 99%
“…It can also disrupt the oxide film and has been used for flux free brazing of pure aluminium 3 and TLP bonding of aluminium alloy. 18 Referring to this work, a novel Al-Si-Cu-Ga-Ce interlayer alloy is applied for the TLP bonding of aluminium and its alloy. Compared with the present copper interlayer, the Al-Si-Cu-Ga-Ce interlayer has a lower melting point than the bonding temperature and the same main element as the aluminium substrate.…”
Section: Microstructure Evolution In Tlp Bonding Of Aluminium Alloy U...mentioning
confidence: 99%